Optimalisasi Strategi Pemasaran Produk Portofolio Di BPRS Bina Amanah Satria, Melalui Pendekatan General Electric - M. Irwan Farouki; Risma Nur Hazizah; Siti Aisaturohmaniyah; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to optimize the marketing of portfolio products at BPRS BAS through the General Electric (GE) Matrix approach. This approach combines the analysis of industry attractiveness and business unit strength, allowing for the mapping of each product's strategic position within the portfolio. The method used in this research is quantitative descriptive through in-depth interviews and secondary data. The results show that BPRS BAS has significant opportunities in the Islamic finance industry, particularly in the small business segment, with key strengths in construction financing and deposits. The 'proactive' marketing strategy and product diversification are key to enhancing competitiveness and customer loyalty. Being in the growth quadrant of the GE Matrix, it is recommended that BPRS BAS continue to expand its products and strengthen educational campaigns to increase market penetration.